Gender inequality, female leadership, and aid allocation: A panel analysis of aid for education - Linda Kleemann; Peter Nunnenkamp; Rainer Thiele (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The aid allocation literature has neglected gender-specific needs for aid. We assess the hypothesis that gender inequality in education is more likely to affect the aid allocation of donor countries with female leadership in the relevant ministry. We find no evidence for a needs-based allocation of aid for education. Female as well as male leaders appear to have rewarded countries with more years of schooling of all children, or specifically of girls. Our estimates indicate just minor gender differences in the allocation behaviour.
Keywords: F35; I24; 330; aid allocation; education; gender inequality; female leadership